1997
DOI: 10.1128/jcm.35.10.2464-2471.1997
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the etiology of presumptive feline leprosy by 16S rRNA gene analysis

Abstract: PCR-amplified 16S rRNA gene sequences were obtained directly from tissue specimens from eight cats with presumptive feline leprosy. Acid-fast bacilli were observed in sections from all eight specimens, but culture for mycobacteria was successful for one specimen only. Analysis of the V2 variable region of each 16S rRNA PCR product identified a sequence with 100% nucleotide identity to the sequences of Mycobacterium lepraemurium, Mycobacterium avium, and Mycobacterium paratuberculosis in four of the specimens f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 26 publications
(39 reference statements)
1
65
0
Order By: Relevance
“…18 The causative agent is presumed to be M. lepraemurium ; however, recent studies using the polymerase chain reaction (PCR) have recently demonstrated the presence of other mycobacteria including novel species. 9,10,19,20 A case of feline leprosy involving a 2-year-old-male cat with a solitary lesion of the right forelimb was described in Northern Italy in 1996. 17 The precise, natural transmission of feline leprosy is unknown, but it has been related to bites of infected rats and cats.…”
Section: Introductionmentioning
confidence: 99%
“…18 The causative agent is presumed to be M. lepraemurium ; however, recent studies using the polymerase chain reaction (PCR) have recently demonstrated the presence of other mycobacteria including novel species. 9,10,19,20 A case of feline leprosy involving a 2-year-old-male cat with a solitary lesion of the right forelimb was described in Northern Italy in 1996. 17 The precise, natural transmission of feline leprosy is unknown, but it has been related to bites of infected rats and cats.…”
Section: Introductionmentioning
confidence: 99%
“…16 Although the tissue was submitted to a reference laboratory, culture was not attempted because it has failed to identify a mycobacterial organism in most feline leprosy cases evaluated to date. 4 This is in contrast to other cutaneous mycobacterial diseases of cats caused by M. ulcerans, M. avium, members of the M. tuberculosis complex (M. bovis and M. microti) or rapidly growing mycobacteria, for which tissue culture permits identification of the species and, most importantly, subsequent in vitro antimicrobial susceptibility testing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, methanol-fixed and DiffQuik-stained smears of FNA samples diagnosed cytologically with mycobacterial infection have been used to amplify DNA in cases of NSB or AFB being abundant in dogs and cats. 23 PCR testing can help distinguish the different potential mycobacterial pathogens 1,3,4,24 and closely related infectious agents such as Nocardia spp. 25 Definitive diagnosis requires differentiation of the Mycobacterium spp., because treatment will depend on the mycobacterial agent involved, even if it has not been well defined by the peer-reviewed literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations